PERAN ORGANISASI FAUNA & FLORA INTERNATIONAL (FFI) PADA PROYEK KONSERVASI HUTAN DI KAWASAN TAMAN NASIONAL KERINCI SEBLAT INDONESIA (TNKS) - Dealina Arfiany Shanur; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is talking about an international organization called Fauna & Flora International (FFI). Fauna & Flora International (FFI) is an organization not only concern about conservation but also taking care biodiversity issues. FFI has a mission preserve threatened species and ecosystems throughout the world, choosing sustainable solutions based on sustainable science and taking into human needs. In Indonesia, FFI works in close partnership with the Ministry of Environment and Forestry of the Republic of Indonesia and has several site projects, one of it is on Kerinci Seblat National Park (KSNP). In general, FFI's activities inside KSNP are related to protected fauna conservation, such as Sumatran Tiger, Helmeted Hornbill and Malay Pangolin. On Kerinci Seblat site project, a task force called the Tiger Protection and Conservation Unit (TPCU) that operates under the direction of KSNP authorities was formed to doing this project. This scientific writing is describe how Fauna & Flora International (FFI) and KSNP authorities are together implementing their vision and mission into an activities related to the conservation of this outstanding National Park. This research, used qualitative methods to collect data from sources and literature studies. The role of Fauna and Flora International giving the good changes for overcoming or minimizing the crime of hunting protected animals and illegal logging. Also providing new insights for local residents about the importance of tigers in the food chain and not count it as a pest that must be destroyed. Keyword : Role, International Organisation, FFI, KNSP, TPCU, Conservation, Tiger